2016
DOI: 10.1097/jcn.0000000000000313
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With the Hospital Arrival Time in Patients With Ischemic Stroke in Korea

Abstract: Nationwide efforts are needed to promote public awareness of stroke and to develop strategies to reduce prehospital delay time for ischemic stroke patients, particularly those who reside in rural areas in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
2
8
1
Order By: Relevance
“…The patients’ perception of symptom severity and prior stroke knowledge directly affected decision delay and indirectly affected prehospital delay in this study. The findings from previous studies also reported consistent relationships between patients perceiving their symptoms as severe and immediate treatment-seeking decisions (Iversen et al, 2020; Sim et al, 2016). The influence of stroke knowledge on delay times is still debated because some researchers measured knowledge of stroke using a single question (Faiz et al, 2014; Geffner et al, 2012; Iversen et al, 2020).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The patients’ perception of symptom severity and prior stroke knowledge directly affected decision delay and indirectly affected prehospital delay in this study. The findings from previous studies also reported consistent relationships between patients perceiving their symptoms as severe and immediate treatment-seeking decisions (Iversen et al, 2020; Sim et al, 2016). The influence of stroke knowledge on delay times is still debated because some researchers measured knowledge of stroke using a single question (Faiz et al, 2014; Geffner et al, 2012; Iversen et al, 2020).…”
Section: Discussionsupporting
confidence: 73%
“…Prehospital treatment-seeking delay is defined as the time from symptom onset to hospital arrival (Powers et al, 2019). Some investigators (Keskin et al, 2005; Sim et al, 2016) have divided prehospital delay into patient/bystander decision delay (the time between stroke symptom onset and a decision to seek treatment) and transportation delay (the time between a decision to seek treatment and hospital arrival). However, the definition of symptom onset varies, especially if the patient awoke with stroke symptoms (Faiz et al, 2014; Keskin et al, 2005).…”
Section: Treatment-seeking Decision After Stroke Symptomsmentioning
confidence: 99%
“…The interval between the onset of symptoms and the arrival at the hospital greatly influences the treatment efficacy and the final prognosis of the patient [10]. Most of the studies on prehospital delay (PHD) have focused on the identification of the socio-demographic, clinical, and contextual characteristics of patients who choose not to seek immediate treatment [11,12,13,14]. However, the PHD can also be affected by other behavioral and cognitive factors and features that have hardly been studied [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among 233 patients who were enrolled in a large-scale study, 160 patients who had arrived at the hospital within 72 h after symptom onset were included in the data analysis. Details about the large-scale study are reported elsewhere [35]. Briefly, the inclusion criteria of the 233 patients were as follows: diagnosed with nontraumatic AIS by brain-computed tomography or magnetic resonance imaging; had been admitted to the hospital for at least one month; and had no severe cognitive impairment or communication difficulties, as determined by neurologists at the hospital.…”
Section: Methodsmentioning
confidence: 99%